2011
DOI: 10.1007/s00535-011-0436-4
|View full text |Cite
|
Sign up to set email alerts
|

Platelet count for predicting fibrosis in nonalcoholic fatty liver disease

Abstract: The platelet count may be an ideal biomarker of the severity of fibrosis in NAFLD patients, because it is simple, easy to measure and handle, cost-effective, and accurate for predicting the severity of fibrosis. Furthermore, by using the platelet count cutoff value validated in our multiple large trials, efficient recruitment of NAFLD patients may be facilitated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
118
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 118 publications
(136 citation statements)
references
References 31 publications
(31 reference statements)
7
118
1
Order By: Relevance
“…However, the significance of the severity of thrombocytopenia in patients with CLDs of other causes is uncertain. Yoneda et al [4] reported a significant negative correlation between the platelet count and the severity of liver fibrosis in patients with nonalcoholic fatty liver disease (NAFLD), based on the results of a multicenter retrospective cohort study. In this paper, the platelet count was higher among patients with NAFLD-related severe fibrosis or cirrhosis than in previously reported patients with HCV-related severe fibrosis or cirrhosis.…”
Section: Dear Editormentioning
confidence: 99%
“…However, the significance of the severity of thrombocytopenia in patients with CLDs of other causes is uncertain. Yoneda et al [4] reported a significant negative correlation between the platelet count and the severity of liver fibrosis in patients with nonalcoholic fatty liver disease (NAFLD), based on the results of a multicenter retrospective cohort study. In this paper, the platelet count was higher among patients with NAFLD-related severe fibrosis or cirrhosis than in previously reported patients with HCV-related severe fibrosis or cirrhosis.…”
Section: Dear Editormentioning
confidence: 99%
“…Platelet count is an [96] BAAT score Age, BMI, ALT, triglycerides Weighted sum √ Ratziu et al [97] BARD score BMI, AST, ALT, DM Ⅱ Weighted sum √ Harrison et al [98] Cirrhosis discrimination score AST, ALT, platelet count, INR Weighted sum × Udell et al [99] FIB-4 index Age, AST, ALT, platelet count Algorithm √ Shah et al [100] Fibrosis probability index Age, AST, previous alcohol use, HOMA-IR, cholesterol Algorithm × Sud et al [101] Forns index Age, platelet count, GGT, cholesterol Algorithm √ Forns et al [102] Gholam's score ALT, HbA1C Weighted score √ Gholam et al [53] Hui model BMI, bilirubin, albumin, platelet count Algorithm × Hui et al [103] King score Age, AST, platelet count, INR Algorithm × Cross et al [104] Lok index AST, ALT, platelet count, INR Algorithm × Lok et al [105] NAFLD fibrosis score Age, BMI, platelet count, albumin, AAR, IFG/DM Ⅱ Algorithm √ Angulo et al [106] NAFLD ideal biomarker for the prediction of advanced fibrosis in many chronic liver diseases [117] and features in multiple composite models currently available to the clinician. The clinical relevance of the AST to platelet ratio index (APRI) as a simple screening tool to predict advanced fibrosis has been demonstrated in the resource-limited South African setting, comparing favourably to the NFS with superior accuracy to the AAR [96] .…”
Section: Markers Of Impaired Hepatic Functioningmentioning
confidence: 99%
“…NAFLD was associated with thrombocytopenia presently and has been described previously. 16,17 Additionally, the association of steatosis with schistosomiasis may aggravate liver disease, increasing the frequency of fibrosis, portal hypertension and liver cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23][24][25] Yoneda et al and Ruiz-Arguelles et al concluded that NAFLD should be considered as a cause of thrombocytopenia. 16,17 Normally, the spleen stores one-third of the platelets that are produced in the body, maintaining a balance with the circulating platelets. Patients with cirrhosis, schistosomiasis, portal hypertension or splenomegaly may have significant degrees of "apparent" thrombocytopenia (with or without leukopenia and anemia), but they rarely have clinical bleeding, since their total platelet mass is usually normal.…”
Section: Discussionmentioning
confidence: 99%